PENGARUH PEMBERDAYAAN DAN DUKUNGAN SOSIAL TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM PENATAAN RUANG DAN PERUMAHAN RAKYAT PROVINSI KALIMANTAN TIMUR - Hidayah, Naniek Naniek ] (EKONOMIA, 2019)
The Influence of Empowerment and Social Support on the Performance of Employees of the Public Works Agency for Spatial Planning and Public Housing of East Kalimantan Province "under the guidance of Ms. Theresia Militina as Advisor Lecturer I and Ms. Suyatin as Supervisor II.            The analysis tool and hypothesis testing in this study used multiple regression analysis or multiple regression consisting of simultaneous tests (simultaneous tests) and partial tests (each test). The process of analyzing data uses SPSS statistical tools.             Empowerment (X1) has a positive and significant effect on the Performance of Employees of the Public              Works Office for Spatial Planning and Public Housing of East Kalimantan Province. So it is known that Empowerment has a positive and significant effect on performance.            Social Support (X2) has a positive and significant effect on the Performance of Employees of the Public                        Works Office in the Spatial Planning and Housing of East Kalimantan Province.  This is because there are positive and significant  influences between the two variables. Through multiple  correlation it can also be seen the effect of social support on performance and indicates that there is a positive relationship between the two variables.          The results showed that Empowerment and Social Support had a positive and significant influence on the Employee Performance of the Public Works Agency in the Spatial Planning and Housing of East Kalimantan Province.